Correlation of acrylamide with precursors and colour in frozen par-fried french fries - Baroogh, Babak Hatami (2012)
The aim of this study was to verify the occurrence of acrylamide formation after final frying and to study the correlation of acrylamide content with amino acids, reducing sugars and moisture content in frozen French fries samples, also to investigate acrylamide formation and reducing sugar content as main precursor in different production date and production plant of frozen fried French fries samples. Acrylamide analysis was based on gas chromatographic mass spectrometric technique (GC-MS) that included extraction and derivatization before analysis. Amino acids and reducing sugars determination has been done using high performance liquid chromatography (HPLC). It was discovered that final frying generates 76.04-348.55 μg/kg of acrylamide in French fries samples by wide range of reducing sugar content in the form of fructose and glucose (0.11-1.30 and 0.096-1.294 mg/g, respectively) and fifteen free amino acids (0.01-9.17 mg/g) that had been detected in frozen French fries sample before final frying. Although, asparagine content (2.76-9.17 mg/g) was higher among other free amino acids, however; threonine and glutamine showed the higher correlation with acrylamide content. In addition, among reducing sugars, there was a significant correlation between glucose and acrylamide content and acrylamide and color development (a). It can be concluded correlation of acrylamide and precursors in frozen par fried French fries samples is not same as fresh fried potatoes. In second part, it has been investigated that there was not a significant difference between means of acrylamide content and reducing sugars of different brand (P > 0.05) and was no significant difference (P > 0.05) between reducing sugars and acrylamide content of two harvest years (2008-2009), although; acrylamide content in 2009 was higher than 2008. This part of study indicated that climate change from 2008 to 2009 has no significant single effect on acrylamide content in this product. Acrylamide content formed after frying frozen French fries sample of twelve month production within these two years are significantly different (P < 0.05). The highest content of acrylamide (348.55μg/kg) was found in samples produced in January that were significantly different among other months. The lowest amount of acrylamide (76.04μg/kg) was found in samples produced in September.